Preparation of Chitosan-Gelatin Sustained-Release Film Incorporated with Resveratrol-Loaded Emulsion and Its Preservation Effect on Prepared Steak - DU Liying, REN Guoyan, ZHAO Bing, SHI Yuxuan, CHENG Xiaoyu (Shipin Kexue, 2025)
In order to develop efficient preserving materials for meat products, sustained-release preservative composite films (CS-GEL-PE) were prepared by casting a mixed solution of chitosan (CS) and gelatin (GEL) added with different volume proportions (2%, 4%, 6% and 8%) of Pickering emulsion (PE) loaded with resveratrol (RES). The microstructure and physical properties of the films were determined by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and an intelligent electronic tensile testing machine, and antioxidant activity, sustained-release performance, and their preservation effect on prepared steak was analyzed. It was found that the addition of PE did not alter the structure of the CS-GEL film, increased its thickness, density, tensile strength, elongation at break, and antioxidant activity while conferring the composite film good sustained-release performance and significantly reducing its water content, solubility, swelling rate and water vapor permeability. The composite film with 6% PE (PE6) had the best overall performance. The preservation effect of the PE6 film combined with vacuum packaging on prepared steak was evaluated using vacuum packaging as a control. After 9 days of storage, the pH of the control group exceeded 6.7, the total volatile basic nitrogen (TVB-N) content was 20.28 mg/100 g, and the total bacterial count (TBC) was 6.37 (lg(CFU/g)), indicating that the steak was spoiled. In contrast, none of the pH, thiobarbituric acid reactive substances (TBARS) value, TVB-N content, and TBC of the PE6 group exceeded the limits, and the preservation effect of the PE6 film was better than the CS-GEL-RES film. In summary, the PE6 film has excellent mechanical properties and can prolong the shelf life of prepared steak.